2008
DOI: 10.1007/s00402-008-0750-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for local control of extremity and trunk desmoid tumors

Abstract: These results suggest that radical surgical treatment causing severe functional impairment should be avoided in selected cases on the basis of patient characteristics, and that other novel therapeutic tools may be necessary for patients in whom a higher risk of local recurrence is assumed or severe complications after surgical treatment are predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 22 publications
4
43
4
Order By: Relevance
“…However, previous studies have reported inconsistent results regarding the association between the microscopic margin status and the recurrence rate [2][3][4][5][6][7][8][9]. No definitive conclusion has been reached regarding the significance of the histological margin status.…”
Section: Introductionmentioning
confidence: 85%
“…However, previous studies have reported inconsistent results regarding the association between the microscopic margin status and the recurrence rate [2][3][4][5][6][7][8][9]. No definitive conclusion has been reached regarding the significance of the histological margin status.…”
Section: Introductionmentioning
confidence: 85%
“…Until 2003, patients with extraperitoneal desmoid tumors were surgically treated with wide surgical margins; however, an unsatisfactory recurrence rate, even in cases with microscopically negative margins (9), prompted a treatment change to meloxicam, a COX-2 inhibitor, from 2003 onwards, based on the results of a study using genetically modified mice (16). Meloxicam treatment for patients with extraperitoneal desmoid tumors was approved by the Institutional Review Board of the Center for Advanced Medicine and Clinical Research of Nagoya University (Nagoya, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…This type of tumor does not metastasize, but is highly locally invasive, and exhibits a propensity for recurrence, even following aggressive surgery with free surgical margin (1). Surgery has been the mainstay of treatment for desmoid tumors; however, there has been controversy about the association between the microscopic margin status and recurrence rates (2)(3)(4)(5)(6)(7)(8)(9), and therefore, no definitive conclusion has been reached regarding the significance of the histological margin status.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they spread along the fascial planes. A high local recurrence rate is reported in several studies (9)(10)(11)(12). Therefore, in the retrospective studies, radiotherapy (RT) has been suggested for its local control benefits.…”
mentioning
confidence: 99%